Explore space weather and the heliophysics big year through the Community Coordinated Modeling Center’s (CCMC) hands-on tools and collaborations - Resnick, Elana; Lundkvist, Anders; Kuznetsova, Maria M.; Mays, M. Leila; Zheng, Yihua; Yue, Jia; Wiegand, Chiu; Mullinix, Richard; Olsson, Elon; MacDonald, Elizabeth; Edson, Laura Brandt; Gallardo-Lacourt, Bea; et al. (Frontiers in Astronomy and Space Sciences, 2026)
The Community Coordinated Modeling Center (CCMC) at NASA Goddard Space Flight Center has developed comprehensive resources and initiatives to support the Heliophysics Big Year (HBY) during the approach to solar maximum. This paper details the CCMC’s extensive outreach efforts from October 2023 through December 2024, engaging diverse audiences including the general public, educators, and scientific communities. Key activities included partnerships with the Intrepid Museum and American Museum of Natural History, educational presentations reaching over 1,000 physics educators, and specialized workshops for high school teachers. The paper also highlights significant technological enhancements to the CCMC’s visualization capabilities, specifically the improved Integrated Space Weather Analysis (ISWA) system with its global synchronization features and specialized layout options. Additionally, we discuss the collaborative development of OpenSpace, a versatile 3D visualization tool that integrates data from observations, simulations, and space missions to support public engagement through planetarium shows and educational initiatives. Through these combined efforts, the CCMC has established multiple pathways for audiences to engage with heliophysics research and better understand space weather phenomena during this period of heightened solar activity.